Impact of Public Distribution System on poverty and food security in India - Kumar, Anjani; Shinoj, P; Joshi, P K (Indian Farming, 2018)
The impact of PDS in tackling under-nutrition was found to deepen across successive rounds of the survey. The contribution of PDS in reducing poverty and improving food security has improved over time. However, persisting imperfections in the system still pose substantial challenges to be tackled for improving cost effectiveness of the PDS services. This necessitates proactive and systematic attempts to improve the functioning of the PDS through introduction of new technologies continually. No doubt, despite recent controversies on effectiveness of PDS, the analyses by the authors clearly suggest that PDS has contributed substantially in reducing poverty, food and nutrition insecurity in the country.